2016
DOI: 10.1080/1064119x.2016.1227406
|View full text |Cite
|
Sign up to set email alerts
|

Piled embankment to prevent damage to pipe buried in soft grounds undergoing lateral flow

Abstract: Lateral flow of soft ground occurs when embankment filling is performed on reclaimed land of foreshore. If a utility pipe is buried in soft ground undergoing the lateral flow, severe damage to the pipe can be caused. A pile-supported embankment has been used to support embankment to minimize lateral flow of the soft soil by transferring the embankment loads through the piles to the firm layer. To prevent damage to the buried pipe subjected to lateral force of the soft ground, full-scale field experiments on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…These lead to the increase of the risk of suffering from various adverted soil-related phenomena. Some of them are: crossing the ground faults [1], [2], land sliding [3,4], tunnel constructing [5], [6] or deformation of the soil due to the appearance of the embankment [7], [8], [9]. Among these threads, the use of embankment on soft soil is recorded as a significant reason for failure to be occurred, which needs reinforcement for the natural soil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These lead to the increase of the risk of suffering from various adverted soil-related phenomena. Some of them are: crossing the ground faults [1], [2], land sliding [3,4], tunnel constructing [5], [6] or deformation of the soil due to the appearance of the embankment [7], [8], [9]. Among these threads, the use of embankment on soft soil is recorded as a significant reason for failure to be occurred, which needs reinforcement for the natural soil.…”
Section: Introductionmentioning
confidence: 99%
“…Among these threads, the use of embankment on soft soil is recorded as a significant reason for failure to be occurred, which needs reinforcement for the natural soil. For instance, Hong et al in [7] has reported the experiments that the lateral displacement of pipe can be up to 200 mm after 30 days. The reinforcement using columns in the soft soil thus proposed as the solution for mitigated approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capped piles are frequently used in pile-supported embankments [4] or pile-net composite foundations [5]. Engineering experiences had shown that composite foundations with capped piles effectively reduced the settlement and the failure of embankments on soft soils [6][7][8][9], especially in highspeed railway and highway engineering [10,11].…”
Section: Introductionmentioning
confidence: 99%